A combined theoretical and experimental study to improve the thermal stability of recombinant D‐lactate dehydrogenase immobilized on a novel superparamagnetic Fe3O4NPs@metal–organic framework. (2nd March 2020) - Torkzadeh‐Mahani, Mahdieh; Zaboli, Maryam; Barani, Mahmood; Torkzadeh‐Mahani, Masoud
Abstract: Lactate dehydrogenase (LDH) is an enzyme that catalyzes the reduction of nicotinamide adenine dinucleotide (NADH) and pyruvate to nicotinamide adenine dinucleotide (NAD + ) and D‐lactate in the final step of anaerobic glycolysis. This enzyme belongs to the family of oxidoreductases. Humans possess two isoforms of LDH enzyme: NAD‐dependent L‐lactate dehydrogenase (L‐LDH) and NAD‐dependent D‐lactate dehydrogenase (D‐LDH). D‐LDH is released during tissue damage, and is a sign of diseases such as kidney stones, heart failure, and some types of cancers and appendicitis. Accordingly, the design and construction of biosensors for the determination of lactate levels are important. The thermal sensitivity of D‐LDH and low protein production in the host bacteria limit the use of this protein in certain applications. To solve these problems, two solutions were used in this study. First, the codon‐optimized 1008 bp D‐LDH gene fused with a histidine tag was cloned at the NcoI/XhoI sites and expressed in E. coli BL21. Second, a new metal–organic framework (Fe3 O4 NPs@Ni‐MOF) was synthesized and used for immobilization and stabilization of D‐LDH. Fe3 O4 NPs@Ni‐MOF core‐shell nanocomposites were characterized by Fourier transform infrared spectroscopy, vibrating sample magnetometer, scanning electron microscopy, X‐ray diffraction, and the Brunauer–Emmett–Teller method. In comparison with the free enzyme, the immobilized enzyme presented better stability at high temperatures. The immobilization of the enzyme could be useful because most reactions happen at high temperatures in industry. To examine the effect of Fe3 O4 NPs@Ni‐MOF on the adsorption and conformation of D‐LDH at the atomistic level, a molecular dynamics simulation was carried out. Our study showed that the interaction between Fe3 O4 NPs@Ni‐MOF and D‐LDH involved van der Waals interactions, hydrophobic interaction energies, cation–π interaction between the Ni ions of the MOF with the enzyme residues and also, the hydrogen bond interactions between enzyme and heteroatoms in the MOF. Root mean square fluctuation and secondary structure analysis showed that Fe3 O4 NPs@Ni‐MOF protected the conformation of the enzyme. Abstract : A combined theoretical and experimental study to improve the thermal stability of recombinant D‐lactate dehydrogenase immobilized on a novel superparamagnetic Fe3 O4 NPs@metal–organic framework